SARS-CoV-2 virus and antibodies in front-line Health Care Workers in an acute hospital in London: preliminary results from a longitudinal study - Catherine Houlihan; Nina Vora; Thomas Byrne; Dan Lewer; Judith Heaney; David Moore; Rebecca Matthews; Sajida Adam; Louise Enfield; Abigail Severn; Angela McBride; Moira J. Spyer; et al. (2020)
Abstract Background Although SARS-CoV-2 infection in Healthcare Workers (HCWs) is a public health concern, there is little description of their longitudinal antibody response in the presence or absence of SARS-CoV-2 and symptoms. We followed HCWs in an acute London hospital to measure seroconversion and RNA detection at the peak of the pandemic. Methods We enrolled 200 patient-facing HCWs between 26 March and 8 April 2020 and collected twice-weekly self-administered nose and throat swabs, symptom data and monthly blood samples. Swabs were tested for SARS-CoV-2 by PCR, and serum for antibodies to spike protein by ELISA and flow cytometry. Findings During the first month, 42/200 (21%) HCWs were PCR positive in at least one nose and throat swab. Only 8/42 HCW (19%) who were PCR positive during the study period had symptoms that met current case definition. Of 181 HCWs who provided enrollment and follow-up blood samples, 82/181 (45.3%) were seropositive. In 33 HCWs who had positive serology at baseline but were PCR negative, 32 remained PCR negative. One HCW had a PCR positive swab six days after enrollment, likely representing waning infection. Conclusion The high seropositivity and RNA detection in these front-line HCWs brings policies to protect staff and patients into acute focus. Our findings have implications for planning for the ‘second wave’ and for vaccination campaigns in similar settings. The evidence of asymptomatic SARS-CoV-2 infection indicates that asymptomatic HCW surveillance is essential, while our study sets the foundations to answer pertinent questions around the duration of protective immune response and the risk of re-infection.